The Concept of Islamic State in the Thought of Rasheed Rida through al Manar: Ottoman Caliphate as Model - Abdoul Karim Toure; Mualimin Mochammad Sahid; Shumsudin Yabi (Universiti Sains Islam Malaysia, 2024)
This study is an attempt to know the view of Rashid Rida through his book Al Manar about the concept of Islamic State. The Islamic State passed through a long and different stages from the Prophetic era, the four Caliphates, the two Dynasties Umayyad and Abbasid and the Ottoman Caliphate before its collapse. This long mix stages between strengths and weaknesses ended by the collapse of Ottoman Caliphate. Rashid Rida, tried hard to save in his capacity the Ottoman Caliphate but failed, he then indirectly describe it in many occasions with some descriptions which show that he was not satisfied with the State for some political and social reasons. The method upon which the study is based is inductive method. The researchers elaborated in the study the concept of Islamic state from Rashid Rida perspective from his Tafsir al- Manar. And among the findings of the study is that, as a scholar we should know that unity of the state is the solid ground of the implimentation of the rule of Allah, therefore it should always be the priority of the time.